(untitled) (Tempo e Argumento, 2024)
The aim of this paper is to analyze the meanings of memory, cultural heritage and the uses of the past in contemporary Ukraine. In order to do so, it sought to analyze how the memory-cultural heritage-politics relationship operates through some examples of patrimonialization and exhibitions on display in three museums in Kiev: the first at the Maidan Museum with objects collected in war zones; the second at the National Museum of History of Ukraine in the Second World War called Ukraine – Crucifixion; and the third at the Museum of War Fragments. All three exhibitions take place simultaneously with the state of war in which Ukraine has been plunged since February 24, 2022 with the Russian invasion of the country. The aim was to analyze how the notions of museum and memory are articulated when the present is still in progress, suggesting a new relationship with time. In view of the wartime context in the country, the reflections presented in this article are the result of an observation of the materials available on the websites of the museum institutions mentioned, as well as journalistic articles published in the international press.